Avaliação da sustentabilidade das unidades de produção familiar da Microbacia do Rio Verde - Município de Marmeleiro - PR - Targanski, Heros (2015)
The global discussion of the development so led to the birth of the concept of sustainable development, which consists of three key dimensions: economic, social and environmental. In order to assess the sustainability of Family Production Units (UPFs) in Rio Verde Basin, in the economic, social and environmental dimensions, were carried out questionnaires applications and observations of 30 UPFs this watershed; before evaluation of UPFs was carried out a literature study to the general understanding of the concept of Sustainable Development. The UPFs of the Rio Verde Basin were divided into three strata of areas (less than 20 ha, between 20 and 30 ha, and greater than 30 ha), making comparisons between they. In the economic dimension were evaluated indicators related to education, to management, to gross and net revenues, to costs, to equity and to debt. The social dimension, evaluated the total household income, the education of residents, the training, the technical assistance, the residences, the water source of the residences, the fate of solid waste, the participation in collective entities, the family succession and the leisure. In the environmental dimension, evaluated the indicators system of planting, soil erosion, terraces, crop rotation, organic fertilizer, disposal of solid waste, animal waste, percentage of native forest and use of chemical fertilizers and pesticides. It was observed that the properties of the lower strata can be considered less sustainable in relation to the properties of the largest strata in the economic, environmental and social dimensions